Mobile Service Users’ Switching Decisions: Case of Libya - Ghnegiwa, Mohamed B.A.E. (Eastern Mediterranean University, 2022)
Efficient Customer Relationship Management is important to ensure long-term customer retention in the telecommunication sector, specifically in Mobile Service Sector. Therefore, it’s important to understand the switching behavior of consumers in regards to their decision to switch from one Mobile Service Provider to another. The analysis of the switching behavior, taking into account multiple factors like quality of the service, network coverage, and more, is crucial to determine the churn decision of the customers. Equally important is to identify potential switching barriers, like switching costs, which deter or delay the switching decision of customers from one service provider to another. This study takes into account Mobile Service Providers and their customers in Libya. The sample size includes individuals from all ages, occupation, and classes. There are 3 main Mobile Service Providers in Libya named Almadar, LTT, and Libyana. There are various factors like price rates, network quality and coverage, quality of customer service which have a significant impact on the switching decision of customers in Libya. These various factors which have been taken into consideration have revealed that the the level of satisfaction among the mobile service users in Libya is low. Moreover, the paper identifies six potential switching barriers like search costs, attractiveness of alternatives, loss of social bonds, functional risks, setup costs and loss of special treatment benefits which force the customers to stay with their existing Mobile Service Provider in Libya. The study intends to enlighten the Mobile Service Providers on how they can ensure effective customer relationship management to control customer retention or churn rate by helping these providers understand the switching behavior of their customers. Keywords: Switching Behavior, Switching Decision, Mobile Service Providers, Switching Barriers, Customer Retention, Level of Satisfaction.

Etkin Müşteri İlişkileri Yönetimi, özellikle Mobil Hizmet Sektörü başta olmak üzere telekomünikasyon sektöründe uzun süreli müşteri elde tutma sağlamak için önemlidir. Bu nedenle, tüketicilerin bir Mobil Servis Sağlayıcıdan diğerine geçme kararlarıyla ilgili olarak değiştirme davranışlarını anlamak önemlidir. Hizmet kalitesi, ağ kapsamı ve daha fazlası gibi birden çok faktörü hesaba katan anahtarlama davranışının analizi, müşterilerin kayıp kararını belirlemek için çok önemlidir. Müşterilerin bir hizmet sağlayıcıdan diğerine geçiş kararını caydıran veya geciktiren geçiş maliyetleri gibi potansiyel geçiş engellerini belirlemek de aynı derecede önemlidir. Bu çalışma, Mobil Servis Sağlayıcıları ve Libya'daki müşterilerini dikkate almaktadır. Örneklem büyüklüğü, her yaştan, meslekten ve sınıftan bireyleri içerir. Libya'da Almadar, LTT ve Libyana adında 3 ana Mobil Servis Sağlayıcı bulunmaktadır. Libya'daki müşterilerin geçiş kararlarında önemli bir etkiye sahip olan fiyat oranları, ağ kalitesi ve kapsamı, müşteri hizmetlerinin kalitesi gibi çeşitli faktörler vardır. Dikkate alınan bu çeşitli faktörler, Libya'daki mobil hizmet kullanıcıları arasında memnuniyet düzeyinin düşük olduğunu ortaya koymuştur. Ayrıca makale, arama maliyetleri, alternatiflerin çekiciliği, sosyal bağların kaybı, işlevsel riskler, kurulum maliyetleri ve müşterileri Libya'daki mevcut Mobil Servis Sağlayıcılarında kalmaya zorlayan özel tedavi avantajlarının kaybı gibi altı potansiyel geçiş engelini tanımlamaktadır. Çalışma, Mobil Servis Sağlayıcıları, müşterilerinin değiştirme davranışını anlamalarına yardımcı olarak, müşteriyi elde tutma veya kayıp oranını kontrol etmek. için etkili müşteri ilişkileri yönetimini nasıl sağlayabilecekleri konusunda aydınlatmayı amaçlamaktadır. Anahtar Kelimeler: Geçiş Davranışı, Geçiş Kararı, Mobil Servis Sağlayıcılar, Geçiş Engelleri, Müşteriyi Elde Tutma, Memnuniyet Düzeyi.
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2022. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Thesis Tez; Business Administration; Marketing Management; a; marketing; costumer relationship; libya; consumer behavior; Electronic Commerce; Mobile Service Sector; Switching Behavior; Switching Decision; Mobile Service Providers; Switching Barriers; Customer Retention; Level of Satisfaction.